A nosological review of depressive disorders based on observations in clinical practice, Part 2: a working typology for clinicians. (February 2013) - Restifo, Sam
Objective: The purpose of this paper is to examine the essential nosological differentiation between melancholic and non-melancholic forms of depression with a view to promoting a meaningful, working typology for clinicians. The paper primarily comprises observations and reflections drawn from clinical practice. Conclusions: The most specific symptoms of melancholic depression are described, as are the main varieties of non-melancholic 'depression', including demoralisation, grief, loneliness, existential depression and depressive personality.